Management of Pulmonary Embolism with Rheolytic Thrombectomy. Issue 4 (2011) - Ferrigno, Lisa; Bloch, Robert; Threlkeld, Judson; Demlow, Thomas; Kansal, Raman; Karmy-Jones, Riyad
Abstract : BACKGROUND: Catheter thrombectomy combining thrombus destruction with local thrombolysis has been used in patients with pulmonary embolism (PE) who are unstable or have significant right heart dysfunction, but have contraindications to systemic thrombolytic therapy. OBJECTIVES: To assess the outcomes of patients who underwent pulmonary embolectomy using a commercially available thrombectomy device. METHODS: A retrospective chart review of patients who underwent pulmonary embolectomy between March 2007 and August 2009 was performed. Patients were classified as having clinical massive or submassive PE, and moderate or severe right ventricular dysfunction. Data collected included pre- and postprocedure shock index (heart rate divided by systolic blood pressure) and mean pulmonary artery pressure. RESULTS: Sixteen patients with a mean (± SD) age of 54.4±15.8 years underwent embolectomy. Five had clinical massive PE (two in cardiogenic shock) and three of 11 submassive cases had severe right ventricular dysfunction. All were deemed to have contraindications to systemic lysis. Both shock index (1.02±33 preintervention versus 0.71±0.2 postintervention [P=0.001]) and mean pulmonary artery pressure (34.5±9.9 mmHg preintervention versus 27.1±7.1 postintervention [P=0.01]) improved. In the massive PE group, one patient died and two survivors experienced retroperitoneal bleeding and transient renal failure. At follow-up (17.3±7.8 months), two patients in the massive PE group demonstrated evidence of mild cor pulmonale. CONCLUSION: Rheolytic thrombectomy is an effective strategy in managing massive PE, particularly in patients who have well-defined contraindications to systemic lytic therapy. The effectiveness of rheolytic thrombectomy for submassive PE is not as well defined, but warrants a comparison with systemic lytic therapy.